Peran Pondok Pesantren Dalam Pembentukan Karakter Religius Anak Di Desa Mranggonlawang - Mahfud, Abd.; Prasetiya , Benny; Santoso, Subhan Adi (STIT Muhammadiyah Paciran Lamongan, 2022)
This research is motivated by the existence of unfavorable behavior that occurs in society, namely first, the habits of the younger generation today do not have a good religious character in everyday life. Second, the lack of parental attention in shaping the religious character of children so that they have good habits and are inherent in carrying out worship according to Islamic teachings. Roudlotul Hikmah Islamic Boarding School education has a curriculum that prioritizes religious character education in the learning process. This research method uses a descriptive method with a qualitative approach to explore the core of theproblems that occur in research with data collection techniques and using interviews in managing teaching to children. The theories used as references in this study include the theory of religious character education, the theory of management of Islamic boarding schools, and the concept of education outside the Islamic boarding school, namely education from parents. The results of the study were (1) From several interviews conducted on all board of Islamic boardingschool teachers, Roudlotul Hikmah explained that all students experienced development in religious character during their stay at the Islamic boarding school. (2) From interviews conducted with several parents of children, it was explained that all children experienced very drastic changes and developments in carrying out religious activities in daily life, especially when they were at home, so that it became an inherent habit of children in carrying out activities. religion in everyday life. (3) One of the supporting factors in the character education process is the parenting pattern of parents while at home and the pattern of education in Islamic boarding schools.